Quality of Life in Bell's Palsy: Correlation with Sunnybrook and House‐Brackmann Over Time. (28th May 2020) - Bylund, Nina; Hultcrantz, Malou; Jonsson, Lars; Marsk, Elin
Abstract : Objectives: To compare patient‐graded facial and social/well‐being function with physician‐graded facial function in Bell's palsy over time. Study Design: A prospective follow‐up study at two tertiary otorhinolaryngological centers. Methods: A total of 96 patients, 36 women and 60 men, aged 18–77 years, were included. Facial Clinimetric Evaluation (FaCE) scale and Facial Disability Index (FDI) scores were compared with Sunnybrook and House‐Brackmann scores. Results: Inclusion was on mean day 7 (96 patients) and follow‐up on days 53 (81 patients) and 137 (32 patients). Initially, correlations between FaCE total score, FaCE domains, FDI physical function, FDI social/well‐being function and Sunnybrook and House‐Brackmann scores were low to fair, except for FaCE facial movement (r = 0.55). Correlations between FaCE total score and Sunnybrook score were very good to excellent at visits 2 (r = 0.83) and 3 (r = 0.81). Women scored FaCE social and FDI social/well‐being function lower than men, despite similar Sunnybrook scores. Conclusion: In early stages of Bell's palsy, there were low to fair correlations between FaCE/FDI (except for facial movement) and Sunnybrook score. This implies that the design of the quality of life (QoL) instruments is less suited for the acute phase. The high correlations at follow‐ups suggest that the questionnaires can be used for evaluation of QoL over time. Our results indicate that women experience more facial palsy‐related psychosocial dysfunction. Level of Evidence: 4 Laryngoscope, 131:E612–E618, 2021